Enhancing Anti-Tumor Activity of Sorafenib Mesoporous Silica Nanomatrix in Metastatic Breast Tumor and Hepatocellular Carcinoma via the Co-Administration with Flufenamic Acid - Li ZY (Dove Medical Press, 2020)
Zhuo-Yue Li,1,2 Yi-Fan Yin,1,2 Yang Guo,1,2 Hui Li,1,2 Mei-Qi Xu,1,2 Man Liu,1,2 Jing-Ru Wang,1,2 Zhen-Han Feng,1,2 Xiao-Chuan Duan,1,2 Shuang Zhang,1,2 Shuai-Qiang Zhang,1,2 Guang-Xue Wang,2 Ai Liao,2 Shu-Min Wang,3 Xuan Zhang1,2 1Beijing Key Laboratory of Molecular Pharmaceutics and New Drug Delivery Systems, School of Pharmaceutical Sciences, Peking University, Beijing 100191, People’s Republic of China; 2Department of Pharmaceutics, School of Pharmaceutical Sciences, Peking University, Beijing 100191, People’s Republic of China; 3Department of Ultrasound, Peking University Third Hospital, Peking University, Beijing 100191, People’s Republic of ChinaCorrespondence: Xuan ZhangDepartment of Pharmaceutics, School of Pharmaceutical Sciences, Peking University, Xueyuan Road 38, Beijing 100191, People’s Republic of ChinaTel/Fax +86-10-82805765Email xuanzhang@bjmu.edu.cnShu-Min WangDepartment of Ultrasound, Peking University Third Hospital, Peking University, Xueyuan Road 38, Beijing 100191, People’s Republic of ChinaEmail shuminwang2014@163.comIntroduction: Because tumor-associated inflammation is a hallmark of cancer treatment, in the present study, sorafenib mesoporous silica nanomatrix (MSNM@SFN) co-administrated with flufenamic acid (FFA, a non-steroidal anti–inflammatory drug (NSAID)) was investigated to enhance the anti-tumor activity of MSNM@SFN.Methods: Metastatic breast tumor 4T1/luc cells and hepatocellular carcinoma HepG2 cells were selected as cell models. The effects of FFA in vitro on cell migration, PGE2 secretion, and AKR1C1 and AKR1C3 levels in 4T1/luc and HepG2 cells were investigated. The in vivo anti-tumor activity of MSNM@SFN co-administrating with FFA (MSNM@SFN+FFA) was evaluated in a 4T1/luc metastatic tumor model, HepG2 tumor-bearing nude mice model, and HepG2 orthotopic tumor-bearing nude mice model, respectively.Results: The results indicated that FFA could markedly decrease cell migration, PGE2 secretion, and AKR1C1 and AKR1C3 levels in both 4T1/luc and HepG2 cells. The enhanced anti-tumor activity of MSNM@SFN+FFA compared with that of MSNM@SFN was confirmed in the 4T1/luc metastatic tumor model, HepG2 tumor-bearing nude mice model, and HepG2 orthotopic tumor-bearing nude mice model in vivo, respectively.Discussion: MSNM@SFN co-administrating with FFA (MSNM@SFN+FFA) developed in this study is an alternative strategy for improving the therapeutic efficacy of MSNM@SFN via co-administration with NSAIDs.Keywords: sorafenib mesoporous silica nanomatrix, MSNM@SFN, flufenamic acid, FFA, PGE2, AKR1C1, AKR1C3, 4T1/luc, HepG2